2022
DOI: 10.1371/journal.pone.0274611
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory deficits are best predictor of serologic response among individuals infected with SARS-CoV-2

Abstract: Objective Smell and taste alteration are closely linked to infection with SARS-CoV-2 and may be associated with a more indolent disease course. Serologic response rates among individuals with mild disease remains limited. We sought to identify whether chemosensory changes associated with COVID-19 were predictive of a serologic response. Study design Cross-sectional study. Methods The sample consisted of 306 adults (≥18 years old) volunteering for convalescent plasma donation following perceived COVID-19 il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Here, descriptions of each symptom were worded in a clear manner. A similar approach was done in the study by Overdevest et al ( 2022 ), however, questions also accounted for symptoms during COVID-19 illness as well as how often the symptoms were noticed by the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Here, descriptions of each symptom were worded in a clear manner. A similar approach was done in the study by Overdevest et al ( 2022 ), however, questions also accounted for symptoms during COVID-19 illness as well as how often the symptoms were noticed by the participants.…”
Section: Resultsmentioning
confidence: 99%
“…10 Some previous studies have reported associations between demographic characteristics and clinical symptoms during the COVID-19 infection, and antibody titers in infected individuals. [11][12][13][14][15] Symptoms such as fever, [15][16][17][18] cough, 15,17 dyspnea, 15,17 loss of smell or taste, 19 and diarrhea 17 have been identified as potential predictive factors of high-titer antibodies. However, the findings are not consistent.…”
Section: Introductionmentioning
confidence: 99%